Análisis del cartel promocional de la Fiesta de las Flores y Frutas, durante el periodo 1990-2024, en la ciudad de Ambato - Pinos Ramos, Karen Estefanía (2024)
The Fiesta de las Flores y Frutas originated from the earthquake of August 5, 1949, as a response by the people of Ambato to the tragedy, leading to the first celebration on February 17, 1951. The celebration takes place annually, accompanied by a poster designed to reflect its cultural context and essence, aspects that are evident in its slogan. The aim of this project is to analyze the printed posters used to promote the Fiesta de las Flores y Frutas during the period from 1990 to 2024, utilizing editorial design criteria by collecting information to define, evaluate, and determine the application of these criteria in the creation of these posters, as well as their cultural value. The methodology employed involves research on design with a qualitative approach, descriptive, cross-sectional, and explanatory in nature, along with bibliographic and observational modalities. Interviews with specialists and the creators of the posters were conducted, and analysis sheets were created. Ultimately, the project shows a favorable outcome regarding the use of editorial criteria and elements of symbolic and conceptual value in design and cultural preservation.